Logic-algebraic method based and constraints programming driven approach to AGVs scheduling. (9th February 2009) - Bocewicz, Grzegorz; Bach, Irena; Banaszak, Zbigniew A.
The subject matter of the study is the automated guided vehicle (AGV) operation synchronisation mechanisms in flexible manufacturing systems. The processes examination has to guarantee the collision-free and deadlock-free AGVs flow. The problem of determination of the rules coordinating access of the vehicles to the shared travel route intervals, ensuring the collision-free and deadlock-free execution of the repetitive processes was reduced to determination of the sufficient conditions of the form of a pair (initial state, a set of priority rules). In particular the problem of searching for a pair is defined in the form of the constraint satisfaction problem (CSP) and is solved with use of the logic programming techniques. The inference engine applied in the LAM is then easily implemented in a kind of constraint logic programming language. Proposed approach provides the framework allowing one to take into account both distinct, and imprecise data, in a unified way.